2010
DOI: 10.1097/01.ogx.0000369671.96283.30
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Fetal Asphyxia in Intrahepatic Cholestasis of Pregnancy

Abstract: Oligohydramnios occurs in about 2.3% of pregnancies and is threatening to fetal health. Hydration has been hypothesized to be an effective way of decreasing the occurrence of the condition because the likelihood for oligohydramnios increases with maternal dehydration. Several studies have shown that both serum and oral hydration therapies are effective treatments for oligohydramnios. The amniotic fluid index (AFI) is the most commonly used quantitative indicator of amniotic fluid volume. This randomized contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Our findings of increased risks of adverse perinatal outcomes in ICP are consistent with previous smaller studies that reported preterm delivery, fetal asphyxia, and meconium staining in white‐European and Latina populations . Previous work has led to uncertainty over the risks of stillbirth; early studies suggested an increased risk but were considered subject to case ascertainment bias, while later reports suggested lower rates of stillbirth, largely attributed to policies of active management, with increased antenatal fetal monitoring and elective delivery at around 37 weeks' gestation.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings of increased risks of adverse perinatal outcomes in ICP are consistent with previous smaller studies that reported preterm delivery, fetal asphyxia, and meconium staining in white‐European and Latina populations . Previous work has led to uncertainty over the risks of stillbirth; early studies suggested an increased risk but were considered subject to case ascertainment bias, while later reports suggested lower rates of stillbirth, largely attributed to policies of active management, with increased antenatal fetal monitoring and elective delivery at around 37 weeks' gestation.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings of increased risks of adverse perinatal outcomes in ICP are consistent with previous smaller studies that reported preterm delivery, fetal asphyxia, and meconium staining in white-European and Latina populations. [4][5][6][7][8]23 Previous work has led to uncertainty over the risks of stillbirth; early studies suggested an increased risk but were considered subject to case ascertainment bias, while later reports suggested lower rates of stillbirth, largely attributed to policies of active management, with increased antenatal fetal monitoring and elective delivery at around 37 weeks' gestation. Interestingly, the most recent study of fetal outcomes in ICP showed no significant increase in the number of stillbirths in an actively managed ICP population compared to controls during the study period (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study conducted by Glantz et al 14 in Swedish women was followed by several other studies [15][16][17][18][19][20][21][22][23] (including 10-5477 women) in different populations, including Hispanic, Turkish, Dutch and Swedish women. Although these studies generally support the findings of increased rates of meconium staining of the amniotic fluid, low Apgar scores at 5 minutes and preterm birth, the retrospective nature or small sample size in these studies makes interpretation difficult.…”
Section: Associated Adverse Perinatal Outcomesmentioning
confidence: 99%